Analisis Perbandingan Tingkat Keuntungan Dan Risiko Portofolio Dengan Menggunakan Model Indeks Tunggal Dan CAPM - Achmad, Daniel Noor; Yudha, Andi; Bela, Marita (Jurnal Ilmiah Manajemen Kesatuan, 2014)
The purpose of this study is to determine the level of retum and risk from a portfolio using Single Index method and CAPM measured using average yield, while the risk ofportfolio is measured by Single Index model calculated using variance, while the risk is measured using CAPM model by beta value (market risk). The analysis used in this study is comparing results of calculation using formulas both Single Index and CAPM models. The fonnulas include methods to measure the return and risk of a stock portfolio. Beta factor is used to measure the sensitivity of the portfolio to the market and both models use the same calculation. The period of this study is during August 2012 — January 2013 by using index data to determine the level of expected return and the risk of each portfolio. The result shows that the highest average expected return rate in the period ofstudy which using the Single Index Model is owned by Sri-Kehati portfolio that has an average rate of return amount 0.0009 and has as small risk of total consisting in market company risk with an amount of 0.00007. Furthermore the smallest return in average is owned by Pefind025 with the amount of 0.0004 and the highest risk with the amount of 0.00010, and the pefind025 portfolio has the smallest beta. In CAPM model we found that all portfolios has negative return and negative risk premises which means six ofthe portfolios do not meet the expected returns. Keywords: return, risk, beta, Single Index Model, CAPM